2009
DOI: 10.1242/jcs.028175
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional electron microscopy reveals new details of membrane systems for Ca2+ signaling in the heart

Abstract: In the current study, the three-dimensional (3D) topologies of dyadic clefts and associated membrane organelles were mapped in mouse ventricular myocardium using electron tomography. The morphological details and the distribution of membrane systems, including transverse tubules (T-tubules), junctional sarcoplasmic reticulum (SR) and vicinal mitochondria, were determined and presumed to be crucial for controlling cardiac Ca2+ dynamics. The geometric complexity of T-tubules that varied in diameter with frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
239
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(263 citation statements)
references
References 58 publications
22
239
1
1
Order By: Relevance
“…2D shows that the majority of RyRs are found in somewhat larger clusters of Ϸ25 RyRs. Some clusters were incompletely filled with RyRs, an observation consistent with a recent electron microscopic study which has shown interior junctions to be incompletely filled with RyRs (24).…”
Section: Resultssupporting
confidence: 89%
“…2D shows that the majority of RyRs are found in somewhat larger clusters of Ϸ25 RyRs. Some clusters were incompletely filled with RyRs, an observation consistent with a recent electron microscopic study which has shown interior junctions to be incompletely filled with RyRs (24).…”
Section: Resultssupporting
confidence: 89%
“…First we assume that our mean cluster ΔF/F 0 of 1.39 (Figure 1D) corresponds to the average (or most frequent) RyR cluster size estimated from several prior studies that range mostly between 50 and 150 RyR/cluster, which in some high‐resolution cases were clusters of clusters or superclusters 2, 3, 4, 5, 6, 27. The mean ΔF/F 0 of 1.39 is indicated by a vertical broken line in Figure 1E.…”
Section: Resultsmentioning
confidence: 99%
“…Confocal resolution used here cannot directly resolve individual RyRs within a junctional cluster as is possible with superresolution or electron microscopy 2, 3, 4, 5, 6. However, the relative F‐FKBP fluorescence intensity (ΔF/F 0 ) within 250 nm around the local cluster peak intensity (Figure 1D) provides a direct quantitative readout that is proportional to the number of RyRs within that local cluster (or supercluster; Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations